Well-being and mobility: a theoretical framework and literature review focusing on older people - Nordbakke, S; Schwanen, T (Routledge, 2014)
There is an increasing attention for how mobility is associated with well-being amongst people in general and older adults in particular. Comparisons across research projects and articles are, however, hampered by the different understandings and conceptualisations of well-being that are employed. We, firstly, develop a heuristic framework for understanding the concept of well-being, and secondly, use this to explore possible linkages between well-being and mobility and to critically examine the various conceptualisations of well-being in research on mobility in later life. It is argued that future work on well-being and mobility should consider both the objective and the subjective and the hedonic and eudaimonic dimensions of well-being, and should pay detailed attention to the multiple ways in which well-being and its linkages to mobility are context-dependent and shaped by the particularities of time and place.